Determining the thermal resistance of a highly insulated wall containing vacuum insulation panels through experimental, calculation and numerical simulation methods. (November 2021) - Moore, Travis V; Cruickshank, Cynthia A.; Beausoleil-Morrison, Ian; Lacasse, Michael
The purpose of this paper is to investigate the potential for calculation methods to determine the thermal resistance of a wall system containing vacuum insulation panels (VIPs) that has been experimentally characterised using a guarded hot box (GHB) apparatus. The VIPs used in the wall assembly have not been characterised separately to the wall assembly, and therefore exact knowledge of the thermal performance of the VIP including edge effect is not known. The calculations and simulations are completed using methods found in literature as well as manufacturer published values for the VIPs to determine the potential for calculation and simulation methods to predict the thermal resistance of the wall assembly without the exact characterisation of the VIP edge effect. The results demonstrate that disregarding the effect of VIP thermal bridges results in overestimating the thermal resistance of the wall assembly in all calculation and simulation methods, ranging from overestimates of 21% to 58%. Accounting for the VIP thermal bridges using the manufacturer advertised effective thermal conductivity of the VIPs resulted in three methods predicting the thermal resistance of the wall assembly within the uncertainty of the GHB results: the isothermal planes method, modified zone method and the 3D simulation. Of these methods only the 3D simulation can be considered a potential valid method for energy code compliance, as the isothermal planes method requires too drastic an assumption to be valid and the modified zone method requires extrapolating the zone factor beyond values which have been validated. The results of this work demonstrate that 3D simulations do show potential for use in lieu of guarded hot box testing for predicting the thermal resistance of wall assemblies containing both VIPs and steel studs. However, knowledge of the VIP effective thermal conductivity is imperative to achieve reasonable results.